Acute multi-sgRNA knockdown of KEOPS complex genes reproduces the microcephaly phenotype of the stable knockout zebrafish model - Jobst-Schwan, Tilman; Schmidt, Johanna Magdalena; Schneider, Ronen; Hoogstraten, Charlotte A.; Ullmann, Jeremy F. P.; Schapiro, David; Majmundar, Amar J.; Kolb, Amy; Eddy, Kaitlyn; Shril, Shirlee; Braun, Daniela A.; Poduri, Annapurna; et al. (PLoS ONE, 2018)
Until recently, morpholino oligonucleotides have been widely employed in zebrafish as an acute and efficient loss-of-function assay. However, off-target effects and reproducibility issues when compared to stable knockout lines have compromised their further use. Here we employed an acute CRISPR/Cas approach using multiple single guide RNAs targeting simultaneously different positions in two exemplar genes (osgep or tprkb) to increase the likelihood of generating mutations on both alleles in the injected F0 generation and to achieve a similar effect as morpholinos but with the reproducibility of stable lines. This multi single guide RNA approach resulted in median likelihoods for at least one mutation on each allele of >99% and sgRNA specific insertion/deletion profiles as revealed by deep-sequencing. Immunoblot showed a significant reduction for Osgep and Tprkb proteins. For both genes, the acute multi-sgRNA knockout recapitulated the microcephaly phenotype and reduction in survival that we observed previously in stable knockout lines, though milder in the acute multi-sgRNA knockout. Finally, we quantify the degree of mutagenesis by deep sequencing, and provide a mathematical model to quantitate the chance for a biallelic loss-of-function mutation. Our findings can be generalized to acute and stable CRISPR/Cas targeting for any zebrafish gene of interest.
Created from Fastlane, Scopus look-up

Adhesion GPCR Gpr126 (Adgrg6) Expression Profiling in Zebrafish, Mouse, and Human Kidney. - Cazorla-Vázquez, Salvador; Kösters, Peter; Bertz, Simone; Pfister, Frederick; Daniel, Christoph; Dedden, Mark; Zundler, Sebastian; Jobst-Schwan, Tilman; Amann, Kerstin Ute; Engel, Felix (Cells, 2023)
Adhesion G protein-coupled receptors (aGPCRs) comprise the second-largest class of GPCRs, the most common target for approved pharmacological therapies. aGPCRs play an important role in development and disease and have recently been associated with the kidney. Several aGPCRs are expressed in the kidney and some aGPCRs are either required for kidney development or their expression level is altered in diseased kidneys. Yet, general aGPCR function and their physiological role in the kidney are poorly understood. Here, we characterize in detail Gpr126 (Adgrg6) expression based on RNAscope® technology in zebrafish, mice, and humans during kidney development in adults. Gpr126 expression is enriched in the epithelial linage during nephrogenesis and persists in the adult kidney in parietal epithelial cells, collecting ducts, and urothelium. Single-cell RNAseq analysis shows that gpr126 expression is detected in zebrafish in a distinct ionocyte sub-population. It is co-detected selectively with slc9a3.2, slc4a4a, and trpv6, known to be involved in apical acid secretion, buffering blood or intracellular pH, and to maintain high cytoplasmic Ca2+ concentration, respectively. Furthermore, gpr126-expressing cells were enriched in the expression of potassium transporter kcnj1a.1 and gcm2, which regulate the expression of a calcium sensor receptor. Notably, the expression patterns of Trpv6, Kcnj1a.1, and Gpr126 in mouse kidneys are highly similar. Collectively, our approach permits a detailed insight into the spatio-temporal expression of Gpr126 and provides a basis to elucidate a possible role of Gpr126 in kidney physiology.
EVALuna2:539836
Keywords: adhesion GPCR; kidney development; Gpr126; parietal epithelial cell; collecting duct; urothelium; ionocytes; zebrafish; RNAscope

Advillin acts upstream of phospholipase C ϵ1 in steroid-resistant nephrotic syndrome - Rao, Jia; Ashraf, Shazia; Tan, Weizhen; Van Der Ven, Amelie T.; Gee, Heon Yung; Braun, Daniela A.; Feher, Krisztina; George, Sudeep P.; Esmaeilniakooshkghazi, Amin; Choi, Won-Il; Jobst-Schwan, Tilman; Schneider, Ronen; et al. (Journal of Clinical Investigation, 2017)
Steroid-resistant nephrotic syndrome (SRNS) is a frequent cause of chronic kidney disease. Here, we identified recessive mutations in the gene encoding the actin-binding protein advillin (AVIL) in 3 unrelated families with SRNS. While all AVIL mutations resulted in a marked loss of its actin-bundling ability, truncation of AVIL also disrupted colocalization with F-actin, thereby leading to impaired actin binding and severing. Additionally, AVIL colocalized and interacted with the phospholipase enzyme PLCE1 and with the ARP2/3 actin-modulating complex. Knockdown of AVIL in human podocytes reduced actin stress fibers at the cell periphery, prevented recruitment of PLCE1 to the ARP3-rich lamellipodia, blocked EGF-induced generation of diacylglycerol (DAG) by PLCE1, and attenuated the podocyte migration rate (PMR). These effects were reversed by overexpression of WT AVIL but not by overexpression of any of the 3 patient-derived AVIL mutants. The PMR was increased by overexpression of WT Avil or PLCE1, or by EGF stimulation; however, this increased PMR was ameliorated by inhibition of the ARP2/3 complex, indicating that ARP-dependent lamellipodia formation occurs downstream of AVIL and PLCE1 function. Together, these results delineate a comprehensive pathogenic axis of SRNS that integrates loss of AVIL function with alterations in the action of PLCE1, an established SRNS protein.
Created from Fastlane, Scopus look-up

Corticosteroid treatment exacerbates nephrotic syndrome in a zebrafish model of magi2a knockout - Jobst-Schwan, Tilman; Hoogstraten, Charlotte A.; Kolvenbach, Caroline M.; Schmidt, Johanna Magdalena; Kolb, Amy; Eddy, Kaitlyn; Schneider, Ronen; Ashraf, Shazia; Widmeier, Eugen; Majmundar, Amar J.; Hildebrandt, Friedhelm (Kidney International, 2019)
Recently, recessive mutations of MAGI2 were identified as a cause of steroid-resistant nephrotic syndrome (SRNS) in humans and mice. To further delineate the pathogenesis of MAGI2 loss of function, we generated stable knockout lines for the two zebrafish orthologues magi2a and magi2b by CRISPR/Cas9. We also developed a novel assay for the direct detection of proteinuria in zebrafish independent of transgenic background. Whereas knockout of magi2b did not yield a nephrotic syndrome phenotype, magi2a -/- larvae developed ascites, periorbital edema, and proteinuria, as indicated by increased excretion of low molecular weight protein. Electron microscopy demonstrated extensive podocyte foot process effacement. As in human SRNS, we observed genotype/phenotype correlation, with edema onset occurring earlier in zebrafish with truncating alleles (5-6 days post fertilization) versus hypomorphic alleles (19-20 days post fertilization). Paradoxically, corticosteroid treatment exacerbated the phenotype, with earlier onset of edema. In contrast, treatment with cyclosporine A or tacrolimus had no significant effect. Although RhoA signaling has been implicated as a downstream mediator of MAGI2 activity, targeting of the RhoA pathway did not modify the nephrotic syndrome phenotype. In the first CRISPR/Cas9 zebrafish knockout model of SRNS, we found that corticosteroids may have a paradoxical effect in the setting of specific genetic mutations.
Created from Fastlane, Scopus look-up
Keywords: chronic kidney disease; focal segmental glomerulosclerosis; kidney development; podocyte; proteinuria

Discordant Clinical Course of Vitamin-D-Hydroxylase (CYP24A1) Associated Hypercalcemia in Two Adult Brothers With Nephrocalcinosis - Jobst-Schwan, Tilman; Pannes, Andrea; Schlingmann, Karl Peter; Eckardt, Kai-Uwe; Beck, Bodo B.; Wiesener, Michael (Kidney & Blood Pressure Research, 2015)
Hypercalcemia can result in nephrocalcinosis/nephrolithiasis and may lead to renal failure. Idiopathic infantile hypercalcemia is caused by mutations of the CYP24A1 gene, which regulates vitamin D activity. Classically infants present with hypercalcemia. Recently, a number of individuals have been reported with late onset clinical manifestation or late diagnosis in adulthood. All these patients are believed to show hypercalciuria.We report a 24 year old patient of healthy consanguine parents. Genetic analysis was performed by Sanger sequencing of the CYP24A1 gene in the index patient and targeted exon 2 analysis of all other family members.The patient was hospitalized with severe malaise during an acute EBV-infection. He showed hypercalcemia > 3mmol/l and acute, hypovolemic renal failure with profound nephrocalcinosis, but no hypercalciuria. Genetic workup revealed a homozygous loss-of-function mutation p.E143del in the CYP24A1 gene. His clinically asymptomatic brother showed nephrocalcinosis of lesser degree. Repeatedly, low parathyroid hormone levels were detected in both brothers.This family displays the highly variable phenotype of CYP24A1 biallelic mutation carriers. CYP24A1 associated disease is an important differential diagnosis for the workup and counseling of infants as well as adults with hypercalcemia since a proper genetic diagnosis may result in therapeutic consequence
EVALuna2:3793

Diverse molecular causes of unsolved autosomal dominant tubulointerstitial kidney diseases - Wopperer, Florian; Knaup, Karl; Stanzick, Kira J.; Schneider, Karen; Jobst-Schwan, Tilman; Ekici, Arif Bülent; Uebe, Steffen; Wenzel, Andrea; Schliep, Stefan; Schürfeld, Carsten; Seitz, Randolf; Bernhardt, Wanja; et al. (Kidney International, 2022)
Autosomal Dominant Tubulointerstitial Kidney Disease (ADTKD) is caused by mutations in one of at least five genes and leads to kidney failure usually in mid adulthood. Throughout the literature, variable numbers of families have been reported, where no mutation can be found and therefore termed ADTKD-not otherwise specified. Here, we aim to clarify the genetic cause of their diseases in our ADTKD registry. Sequencing for all known ADTKD genes was performed, followed by SNaPshot minisequencing for the dupC (an additional cytosine within a stretch of seven cytosines) mutation of MUC1. A virtual panel containing 560 genes reported in the context of kidney disease (nephrome) and exome sequencing were then analyzed sequentially. Variants were validated and tested for segregation. In 29 of the 45 registry families, mutations in known ADTKD genes were found, mostly in MUC1. Sixteen families could then be termed ADTKD-not otherwise specified, of which nine showed diagnostic variants in the nephrome (four in COL4A5, two in INF2 and one each in COL4A4, PAX2, SALL1 and PKD2). In the other seven families, exome sequencing analysis yielded potential disease associated variants in novel candidate genes for ADTKD; evaluated by database analyses and genome-wide association studies. For the great majority of our ADTKD registry we were able to reach a molecular genetic diagnosis. However, a small number of families are indeed affected by diseases classically described as a glomerular entity. Thus, incomplete clinical phenotyping and atypical clinical presentation may have led to the classification of ADTKD. The identified novel candidate genes by exome sequencing will require further functional validation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: ADTKD; Alport syndrome; exome; MITKD; MUC1; UMOD

GAPVD1 and ANKFY1 mutations implicate RAB5 regulation in nephrotic syndrome - Hermle, Tobias; Schneider, Ronen; Schapiro, David; Braun, Daniela A.; Van Der Ven, Amelie T.; Warejko, Jillian K.; Daga, Ankana; Widmeier, Eugen; Nakayama, Makiko; Jobst-Schwan, Tilman; Majmundar, Amar J.; Ashraf, Shazia; et al. (Journal of the American Society of Nephrology, 2018)
Background Steroid-resistant nephrotic syndrome (SRNS) is a frequent cause of CKD. The discovery of monogenic causes of SRNS has revealed specific pathogenetic pathways, but these monogenic causes do not explain all cases of SRNS. Methods To identify novel monogenic causes of SRNS, we screened 665 patients by whole-exome sequencing. We then evaluated the in vitro functional significance of two genes and the mutations therein that we discovered through this sequencing and conducted complementary studies in podocyte-like Drosophila nephrocytes. Results We identified conserved, homozygous missense mutations of GAPVD1 in two families with early-onset NS and a homozygous missense mutation of ANKFY1 in two siblings with SRNS. GAPVD1 and ANKFY1 interact with the endosomal regulator RAB5. Coimmunoprecipitation assays indicated interaction between GAPVD1 and ANKFY1 proteins, which also colocalized when expressed in HEK293T cells. Silencing either protein diminished the podocyte migration rate. Compared with wild-type GAPVD1 and ANKFY1, the mutated proteins produced upon ectopic expression of GAPVD1 or ANKFY1 bearing the patient-derived mutations exhibited altered binding affinity for active RAB5 and reduced ability to rescue the knockout-induced defect in podocyte migration. Coimmunoprecipitation assays further demonstrated a physical interaction between nephrin and GAPVD1, and immunofluorescence revealed partial colocalization of these proteins in rat glomeruli. The patient-derived GAPVD1 mutations reduced nephrin-GAPVD1 binding affinity. In Drosophila, silencing Gapvd1 impaired endocytosis and caused mistrafficking of the nephrin ortholog. Conclusions Mutations in GAPVD1 and probably in ANKFY1 are novel monogenic causes of NS. The discovery of these genes implicates RAB5 regulation in the pathogenesis of human NS.
Created from Fastlane, Scopus look-up

Gene panel sequencing identifies a likely monogenic cause in 7% of 235 Pakistani families with nephrolithiasis - Amar, Ali; Majmundar, Amar J.; Ullah, Ihsan; Afzal, Ayesha; Braun, Daniela A.; Shril, Shirlee; Daga, Ankana; Jobst-Schwan, Tilman; Ahmad, Mumtaz; Sayer, John A.; Gee, Heon Yung; Halbritter, Jan; et al. (Human genetics, 2019)
Nephrolithiasis (NL) affects 1 in 11 individuals worldwide and causes significant patient morbidity. We previously demonstrated a genetic cause of NL can be identified in 11–29% of pre-dominantly American and European stone formers. Pakistan, which resides within the Afro-Asian stone belt, has a high prevalence of nephrolithiasis (12%) as well as high rate of consanguinity (> 50%). We recruited 235 Pakistani subjects hospitalized for nephrolithiasis from five tertiary hospitals in the Punjab province of Pakistan. Subjects were surveyed for age of onset, NL recurrence, and family history. We conducted high-throughput exon sequencing of 30 NL disease genes and variant analysis to identify monogenic causative mutations in each subject. We detected likely causative mutations in 4 of 30 disease genes, yielding a likely molecular diagnosis in 7% (17 of 235) of NL families. Only 1 of 17 causative mutations was identified in an autosomal recessive disease gene. 10 of the 12 detected mutations were novel mutations (83%). SLC34A1 was most frequently mutated (12 of 17 solved families). We observed a higher frequency of causative mutations in subjects with a positive NL family history (13/109, 12%) versus those with a negative family history (4/120, 3%). Five missense SLC34A1 variants identified through genetic analysis demonstrated defective phosphate transport. We examined the monogenic causes of NL in a novel geographic cohort and most frequently identified dominant mutations in the sodium–phosphate transporter SLC34A1 with functional validation.
Created from Fastlane, Scopus look-up

Genetic variants in the LAMA5 gene in pediatric nephrotic syndrome - Braun, Daniela A.; Warejko, Jillian K.; Ashraf, Shazia; Tan, Weizhen; Daga, Ankana; Schneider, Ronen; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; Majmundar, Amar J.; Nakayama, Makiko; Schapiro, David; et al. (Nephrology Dialysis Transplantation, 2019)
Background. Nephrotic syndrome (NS), a chronic kidney disease, is characterized by significant loss of protein in the urine causing hypoalbuminemia and edema. In general, ∼15% of childhood-onset cases do not respond to steroid therapy and are classified as steroid-resistant NS (SRNS). In ∼30% of cases with SRNS, a causative mutation can be detected in one of 44 monogenic SRNS genes. The gene LAMA5 encodes laminin-a5, an essential component of the glomerular basement membrane. Mice with a hypomorphic mutation in the orthologous gene Lama5 develop proteinuria and hematuria. Methods. To identify additional monogenic causes of NS, we performed whole exome sequencing in 300 families with pediatric NS. In consanguineous families we applied homozygosity mapping to identify genomic candidate loci for the underlying recessivemutation. Results. In three families, in whom mutations in known NS genes were excluded, but in whom a recessive, monogenic cause of NS was strongly suspected based on pedigree information, we identified homozygous variants of unknown significance (VUS) in the gene LAMA5. While all affected individuals had nonsyndromic NS with an early onset of disease, their clinical outcome and response to immunosuppressive therapy differed notably. Conclusion. We here identify recessive VUS in the gene LAMA5 in patients with partially treatment-responsive NS. More data will be needed to determine the impact of these VUS in disease management. However, familial occurrence of disease, data from genetic mapping and a mouse model that recapitulates the NS phenotypes suggest that these genetic variants may be inherited factors that contribute to the development of NS in pediatric patients.
Created from Fastlane, Scopus look-up
Keywords: genetic variants; inherited diseases; nephrotic syndrome; treatment response in pediatric nephrotic syndrome; whole exome sequencing

Hypoxia regulates the sperm associated antigen 4 (SPAG4) via HIF, which is expressed in renal clear cell carcinoma and promotes migration and invasion in vitro - Knaup, Karl; Monti, Juliana; Hackenbeck, Thomas; Jobst-Schwan, Tilman; Klanke, Bernd; Schietke, Ruth Elisabeth; Wacker, Ingrid; Behrens, Jürgen; Amann, Kerstin Ute; Eckardt, Kai-Uwe; Warnecke, Christina; Wiesener, Michael (Molecular Carcinogenesis, 2014)
Hypoxia leads to the upregulation of a variety of genes mediated largely via the hypoxia inducible transcription factor (HIF). Prominent HIF-regulated target genes such as the vascular endothelial growth factor (VEGF), the glucose transporter 1 (Glut-1), or erythropoietin (EPO) help to assure survival of cells and organisms in a low oxygenated environment. Here, we are the first to report the hypoxic regulation of the sperm associated antigen 4 (SPAG4). SPAG4 is a member of the cancer testis (CT) gene family and to date little is known about its physiological function or its involvement in tumor biology. A number of CT family candidate genes are therefore currently being investigated as potential cancer markers, due to their predominant testicular expression pattern. We analyzed RNA and protein expression by RNAse protection assay, immunoflurescent as well as immunohistological stainings. To evaluate the influence of SPAG4 on migration and invasion capabilities, siRNA knockdown as well as transient overexpression was performed prior to scratch or invasion assay analysis. The hypoxic regulation of SPAG4 is clearly mediated in a HIF-1 and VHL dependent manner. We furthermore show upregulation of SPAG4 expression in human renal clear cell carcinoma (RCC) and co-localization within the nucleolus in physiological human testis tissue. SPAG4 knockdown reduces the invasion capability of RCC cells in vitro and overexpression leads to enhancement of tumor cell migration. Together, SPAG4 could possibly play a role in the invasion capability and growth of renal tumors and could represent an interesting target for clinical intervention. © 2013 Wiley Periodicals, In
EVALuna2:3620

Moving beyond GWAS and eQTL Analysis to Validated Hits in Chronic Kidney Disease - Müller-Deile, Janina; Jobst-Schwan, Tilman; Schiffer, Mario (Cell Metabolism, 2019)
Genome-wide association studies (GWAS) have identified multiple chronic kidney disease (CKD)-associated single-nucleotide polymorphisms (SNPs) mainly localized to non-coding genomic regions. To understand which genes and which cell types are affected by these genetic variants, compartment-specific transcriptome, genome, and epigenome data were analyzed in an integrative manner in a recent study by Qiu et al. (Qiu et al., 2018).
EVALuna2:118628

Mutations in KEOPS-complex genes cause nephritic syndrome with primary microcephaly - Braun, Daniela A.; Rao, Jia; Mollet, Geraldine; Schapiro, David; Daugeron, Marie-Claire; Tan, Weizhen; Gribouval, Olivier; Boyer, Olivia; Revy, Patrick; Jobst-Schwan, Tilman; Schmidt, Johanna Magdalena; Lawson, Jennifer A.; et al. (Nature Genetics, 2017)
Galloway-Mowat syndrome (GAMOS) is an autosomalrecessive disease characterized by the combination of earlyonset nephrotic syndrome (SRNS) and microcephaly with brain anomalies. Here we identified recessive mutations in OSGEP, TP53RK, TPRKB, and LAGE3, genes encoding the four subunits of the KEOPS complex, in 37 individuals from 32 families with GAMOS. CRISPR-Cas9 knockout in zebrafish and mice recapitulated the human phenotype of primary microcephaly and resulted in early lethality. Knockdown of OSGEP, TP53RK, or TPRKB inhibited cell proliferation, which human mutations did not rescue. Furthermore, knockdown of these genes impaired protein translation, caused endoplasmic reticulum stress, activated DNA-damage-response signaling, and ultimately induced apoptosis. Knockdown of OSGEP or TP53RK induced defects in the actin cytoskeleton and decreased the migration rate of human podocytes, an established intermediate phenotype of SRNS. We thus identified four new monogenic causes of GAMOS, describe a link between KEOPS function and human disease, and delineate potential pathogenic mechanisms.
Created from Fastlane, Scopus look-up

Mutations in multiple components of the nuclear pore complex cause nephrotic syndrome - Braun, Daniela A.; Lovric, Svjetlana; Schapiro, David; Schneider, Ronen; Marquez, Jonathan; Asif, Maria; Hussain, Muhammad Sajid; Daga, Ankana; Widmeier, Eugen; Rao, Jia; Ashraf, Shazia; Tan, Weizhen; et al. (Journal of Clinical Investigation, 2018)
Steroid-resistant nephrotic syndrome (SRNS) almost invariably progresses to end-stage renal disease. Although more than 50 monogenic causes of SRNS have been described, a large proportion of SRNS remains unexplained. Recently, it was discovered that mutations of NUP93 and NUP205, encoding 2 proteins of the inner ring subunit of the nuclear pore complex (NPC), cause SRNS. Here, we describe mutations in genes encoding 4 components of the outer rings of the NPC, namely NUP107, NUP85, NUP133, and NUP160, in 13 families with SRNS. Using coimmunoprecipitation experiments, we showed that certain pathogenic alleles weakened the interaction between neighboring NPC subunits. We demonstrated that morpholino knockdown of nup107, nup85, or nup133 in Xenopus disrupted glomerulogenesis. Re-expression of WT mRNA, but not of mRNA reflecting mutations from SRNS patients, mitigated this phenotype. We furthermore found that CRISPR/Cas9 knockout of NUP107, NUP85, or NUP133 in podocytes activated Cdc42, an important effector of SRNS pathogenesis. CRISPR/ Cas9 knockout of nup107 or nup85 in zebrafish caused developmental anomalies and early lethality. In contrast, an in-frame mutation of nup107 did not affect survival, thus mimicking the allelic effects seen in humans. In conclusion, we discovered here that mutations in 4 genes encoding components of the outer ring subunits of the NPC cause SRNS and thereby provide further evidence that specific hypomorphic mutations in these essential genes cause a distinct, organ-specific phenotype.
Created from Fastlane, Scopus look-up

Mutations in PRDM15 are a novel cause of galloway-mowat syndrome - Mann, Nina; Mzoughi, Slim; Schneider, Ronen; Kuhl, Susanne J.; Schanze, Denny; Klambt, Verena; Lovric, Svjetlana; Mao, Youying; Shi, Shasha; Tan, Weizhen; Kuhl, Michael; Onuchic-Whitford, Ana C.; et al. (Journal of the American Society of Nephrology, 2021)
Background Galloway-Mowat syndrome (GAMOS) is characterized by neurodevelopmental defects and a progressive nephropathy, which typically manifests as steroid-resistant nephrotic syndrome. The prognosis of GAMOS is poor, and the majority of children progress to renal failure. The discovery of monogenic causes of GAMOS has uncovered molecular pathways involved in the pathogenesis of disease. Methods Homozygosity mapping, whole-exome sequencing, and linkage analysis were used to identify mutations in four families with a GAMOS-like phenotype, and high-throughput PCR technology was applied to 91 individuals with GAMOS and 816 individuals with isolated nephrotic syndrome. In vitro and in vivo studies determined the functional significance of the mutations identified. Results Three biallelic variants of the transcriptional regulator PRDM15 were detected in six families with proteinuric kidney disease. Four families with a variant in the protein’s zinc-finger (ZNF) domain have additional GAMOS-like features, including brain anomalies, cardiac defects, and skeletal defects. All variants destabilize the PRDM15 protein, and the ZNF variant additionally interferes with transcriptional activation. Morpholino oligonucleotide-mediated knockdown of Prdm15 in Xenopus embryos disrupted pronephric development. Human wild-type PRDM15 RNA rescued the disruption, but the three PRDM15 variants did not. Finally, CRISPR-mediated knockout of PRDM15 in human podocytes led to dysregulation of several renal developmental genes. Conclusions Variants in PRDM15 can cause either isolated nephrotic syndrome or a GAMOS-type syndrome on an allelic basis. PRDM15 regulates multiple developmental kidney genes, and is likely to play an essential role in renal development in humans.
Created from Fastlane, Scopus look-up

Mutations in six nephrosis genes delineate a pathogenic pathway amenable to treatment - Ashraf, Shazia; Kudo, Hiroki; Rao, Jia; Kikuchi, Atsuo; Widmeier, Eugen; Lawson, Jennifer A.; Tan, Weizhen; Hermle, Tobias; Warejko, Jillian K.; Shril, Shirlee; Airik, Merlin; Jobst-Schwan, Tilman; et al. (Nature Communications, 2018)
No efficient treatment exists for nephrotic syndrome (NS), a frequent cause of chronic kidney disease. Here we show mutations in six different genes (MAGI2, TNS2, DLC1, CDK20, ITSN1, ITSN2) as causing NS in 17 families with partially treatment-sensitive NS (pTSNS). These proteins interact and we delineate their roles in Rho-like small GTPase (RLSG) activity, and demonstrate deficiency for mutants of pTSNS patients. We find that CDK20 regulates DLC1. Knockdown of MAGI2, DLC1, or CDK20 in cultured podocytes reduces migration rate. Treatment with dexamethasone abolishes RhoA activation by knockdown of DLC1 or CDK20 indicating that steroid treatment in patients with pTSNS and mutations in these genes is mediated by this RLSG module. Furthermore, we discover ITSN1 and ITSN2 as podocytic guanine nucleotide exchange factors for Cdc42. We generate Itsn2-L knockout mice that recapitulate the mild NS phenotype. We, thus, define a functional network of RhoA regulation, thereby revealing potential therapeutic targets.
Created from Fastlane, Scopus look-up

Mutations in sphingosine-1-phosphate lyase cause nephrosis with ichthyosis and adrenal insufficiency - Lovric, Svjetlana; Goncalves, Sara; Gee, Heon Yung; Oskouian, Babak; Srinivas, Honnappa; Choi, Won-Il; Shril, Shirlee; Ashraf, Shazia; Tan, Weizhen; Rao, Jia; Airik, Merlin; Schapiro, David; et al. (Journal of Clinical Investigation, 2017)
Steroid-resistant nephrotic syndrome (SRNS) causes 15% of chronic kidney disease cases. A mutation in 1 of over 40 monogenic genes can be detected in approximately 30% of individuals with SRNS whose symptoms manifest before 25 years of age. However, in many patients, the genetic etiology remains unknown. Here, we have performed whole exome sequencing to identify recessive causes of SRNS. In 7 families with SRNS and facultative ichthyosis, adrenal insufficiency, immunodeficiency, and neurological defects, we identified 9 different recessive mutations in SGPL1, which encodes sphingosine-1-phosphate (S1P) lyase. All mutations resulted in reduced or absent SGPL1 protein and/or enzyme activity. Overexpression of cDNA representing SGPL1 mutations resulted in subcellular mislocalization of SGPL1. Furthermore, expression of WT human SGPL1 rescued growth of SGPL1-deficient dpl1? yeast strains, whereas expression of diseaseassociated variants did not. Immunofluorescence revealed SGPL1 expression in mouse podocytes and mesangial cells. Knockdown of Sgpl1 in rat mesangial cells inhibited cell migration, which was partially rescued by VPC23109, an S1P receptor antagonist. In Drosophila, Sply mutants, which lack SGPL1, displayed a phenotype reminiscent of nephrotic syndrome in nephrocytes. WT Sply, but not the disease-associated variants, rescued this phenotype. Together, these results indicate that SGPL1 mutations cause a syndromic form of SRNS.
Created from Fastlane, Scopus look-up

Mutations in WDR4 as a new cause of Galloway–Mowat syndrome - Braun, Daniela A.; Shril, Shirlee; Sinha, Aditi; Schneider, Ronen; Tan, Weizhen; Ashraf, Shazia; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; Majmundar, Amar J.; Daga, Ankana; Warejko, Jillian K.; et al. (American Journal of Medical Genetics Part A, 2018)
Galloway-Mowat syndrome (GAMOS) is a phenotypically heterogeneous disorder characterized by neurodevelopmental defects combined with renal-glomerular disease, manifesting with proteinuria. To identify additional monogenic disease causes, we here performed whole exome sequencing (WES), linkage analysis, and homozygosity mapping in three affected siblings of an Indian family with GAMOS. Applying established criteria for variant filtering, we identify a novel homozygous splice site mutation in the gene WDR4 as the likely disease-causing mutation in this family. In line with previous reports, we observe growth deficiency, microcephaly, developmental delay, and intellectual disability as phenotypic features resulting from WDR4 mutations. However, the newly identified allele additionally gives rise to proteinuria and nephrotic syndrome, a phenotype that was never reported in patients with WDR4 mutations. Our data thus expand the phenotypic spectrum of WDR4 mutations by demonstrating that, depending on the specific mutated allele, a renal phenotype may be present. This finding suggests that GAMOS may occupy a phenotypic spectrum with other microcephalic diseases. Furthermore, WDR4 is an additional example of a gene that encodes a tRNA modifying enzyme and gives rise to GAMOS, if mutated. Our findings thereby support the recent observation that, like neurons, podocytes of the renal glomerulus are particularly vulnerable to cellular defects resulting from altered tRNA modifications.
Created from Fastlane, Scopus look-up
Keywords: Galloway–Mowat syndrome; Mendelian diseases; rare syndromic diseases; variable phenotypic expressivity; whole-exome sequencing

Panel sequencing distinguishes monogenic forms of nephritis from nephrosis in children - Schapiro, David; Daga, Ankana; Lawson, Jennifer A.; Majmundar, Amar J.; Lovric, Svjetlana; Tan, Weizhen; Warejko, Jillian K.; Fessi, Inés; Rao, Jia; Airik, Merlin; Gee, Heon Yung; Schneider, Ronen; et al. (Nephrology Dialysis Transplantation, 2019)
Background. Alport syndrome (AS) and atypical hemolytic- uremic syndrome (aHUS) are rare forms of chronic kidney disease (CKD) that can lead to a severe decline of renal function. Steroid-resistant nephrotic syndrome (SRNS) is more common than AS and aHUS and causes 10% of childhood-onset CKD. In recent years, multiple monogenic causes of AS, aHUS and SRNS have been identified, but their relative prevalence has yet to be studied together in a typical pediatric cohort of children with proteinuria and hematuria. We hypothesized that identification of causative mutations by whole exome sequencing (WES) in known monogenic nephritis and nephrosis genes would allow distinguishing nephritis from nephrosis in a typical pediatric group of patients with both proteinuria and hematuria at any level. Methods. We therefore conducted an exon sequencing (WES) analysis for 11 AS, aHUS and thrombotic thrombocytopenic purpura-causing genes in an international cohort of 371 patients from 362 families presenting with both proteinuria and hematuria before age 25 years. In parallel, we conducted either WES or high-throughput exon sequencing for 23 SRNS-causing genes in all patients. Results. We detected pathogenic mutations in 18 of the 34 genes analyzed, leading to a molecular diagnosis in 14.1% of families (51 of 362). Disease-causing mutations were detected in 3 AS-causing genes (4.7%), 3 aHUS-causing genes (1.4%) and 12 NS-causing genes (8.0%). We observed a much higher mutation detection rate for monogenic forms of CKD in consanguineous families (35.7% versus 10.1%). Conclusions. We present the first estimate of relative frequency of inherited AS, aHUS and NS in a typical pediatric cohort with proteinuria and hematuria. Important therapeutic and preventative measures may result from mutational analysis in individuals with proteinuria and hematuria.
Created from Fastlane, Scopus look-up
Keywords: genetics; monogenic renal disease; nephritis; nephrotic syndrome; pediatrics

Pharmacodynamic Effect of mTOR Inhibition-based Immunosuppressive Therapy on T- and B-cell Subsets After Renal Transplantation - Wei, Xinyi; Weber, Sabine; Yin, Decheng; Allabauer, Ida; Jobst-Schwan, Tilman; Wiesener, Michael; Schiffer, Mario; Dudziak, Diana; Lehmann, Christian; Wölfle, Joachim; Hörning, André (Transplantation Direct, 2024)
Background. The mammalian target of rapamycin inhibitor (mTORi) therapy after kidney transplantation is solely monitored pharmacokinetically, not necessarily reflecting PI3K-Akt-mTOR pathway blockade efficacy leading to potential under- or overimmunosuppression. Methods. In this cross-sectional study, phosphoflow cytometry was used to determine the efficacy of mTOR inhibition in peripheral T- and B-lymphocyte subsets by assessing p70S6 kinase (p70S6K) phosphorylation in renal transplant recipients upon treatment with a combination of either mTORi and calcineurin inhibitors (n = 18), or mTORi with mycophenolic acid (n = 9). Nine dialysis patients with end-stage renal disease and 17 healthy age-matched volunteers served as controls. Results. mTORi treatment reduced p70S6K phosphorylation in CD4+, CD8+ T, and CD19+ B cells compared with healthy controls (HCs). Subpopulation analysis of CD4+ T cells and CD19+ B cells revealed a significant reduction of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells (P < 0.05), CD24hiCD38hi transitional B cells (P < 0.001), CD24+CD38− memory B cells (P < 0.001), and CD24intCD38int-naive B cells (P < 0.05) upon mTORi treatment, whereas CD4+CD45RA−CD25++CD127− regulatory T cells and CD24−CD38hi plasmablasts were not affected. Compared with mTORi + mycophenolic acid therapy, mTORi + calcineurin inhibitor treatment exhibited an even stronger inhibition of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells and CD8+ T cells. However, trough levels of mTORi did not correlate with p70S6K phosphorylation. Conclusions. mTORi selectively inhibited p70S6K phosphorylation in select lymphocyte subtypes. Assessing p70S6K phosphorylation by phosphoflow cytometry may serve as an approach to understand cell subset specific effects of mTORi providing detailed pharmacodynamic information for individualizing immunosuppression.
CRIS-Team Scopus Importer:2024-07-19

Renal uptake of the antiapoptotic protein survivin is mediated by megalin at the apical membrane of the proximal tubule - Jobst-Schwan, Tilman; Knaup, Karl; Nielsen, Rikke; Hackenbeck, Thomas; Büttner-Herold, Maike; Lechler, Philipp; Kroening, Sven; Goppelt-Strübe, Margarete; Schlötzer-Schrehardt, Ursula; Fuernrohr, Barbara G.; Voll, Reinhard E.; Amann, Kerstin Ute; et al. (American Journal of Physiology-Renal Physiology, 2013)
The inhibitor of apoptosis protein survivin is a bifunctional molecule that regulates cellular division and survival. We have previously shown that survivin protein can be found at high concentrations in the adult kidney, particularly in the proximal tubules. Here, survivin is localized primarily at the apical membrane, a pattern that may indicate absorption of the protein. Several proteins in primary urine are internalized by megalin, an endocytosis receptor, which is in principle found in the same localization as survivin. Immunolabeling for survivin in different species confirmed survivin signal localizing to the apical membrane of the proximal tubule. Immunoelectron microscopy also showed apical localization of survivin in human kidneys. Furthermore, in polarized human primary tubular cells endogenous as well as external recombinant survivin is stored in the apical region of the cells. Costaining of survivin and megalin by immunohistochemistry and immunoelectron microscopy confirmed colocalization. Finally, by surface plasmon resonance we were able to demonstrate that survivin binds megalin and cubilin and that megalin knockout mice lose survivin through the urine. Survivin accumulates at the apical membrane of the renal tubule by reuptake, which is achieved by the endocytic receptor megalin, collaborating with cubilin. For this to occur, survivin will have to circulate in the blood and be filtered into the primary urine. It is not known at this stage what the functional role of tubular survivin is. However, a small number of experimental and clinical reports implicate that renal survivin is important for functional integrity of the kidney. © 2013 by the American Physiological Society.
Created from Fastlane, Scopus look-up
Keywords: Acute kidney injury; Apoptosis; Glomerular filtration; Lysosomes; Proteinuria

Tyrosine Phosphorylation of CD2AP Affects Stability of the Slit Diaphragm Complex - Tossidou, Irini; Teng, Beina; Worthmann, Kirstin; Müller-Deile, Janina; Jobst-Schwan, Tilman; Kardinal, Christian; Schroder, Patricia; Bolanos-Palmieri, Patricia; Haller, Hermann; Willerding, Jonas; Drost, Dana M.; de Jonge, Laura; et al. (Journal of the American Society of Nephrology, 2019)
BACKGROUND: CD2-associated protein (CD2AP), a slit diaphragm-associated scaffolding protein involved in survival and regulation of the cytoskeleton in podocytes, is considered a "stabilizer" of the slit diaphragm complex that connects the slit diaphragm protein nephrin to the cytoskeleton of the cell. Tyrosine phosphorylation of slit diaphragm molecules can influence their surface expression, but it is unknown whether tyrosine phosphorylation events of CD2AP are also physiologically relevant to slit diaphragm stability. METHODS: We used isoelectric focusing, western blot analysis, and immunofluorescence to investigate phosphorylation of CD2AP, and phospho-CD2AP antibodies and site-directed mutagenesis to define the specific phosphorylated tyrosine residues. We used cross-species rescue experiments in Cd2apKD zebrafish and in Drosophila cindrRNAi mutants to define the physiologic relevance of CD2AP phosphorylation of the tyrosine residues. RESULTS: We found that VEGF-A stimulation can induce a tyrosine phosphorylation response in CD2AP in podocytes, and that these phosphorylation events have an important effect on slit diaphragm protein localization and functionality in vivo. We demonstrated that tyrosine in position Y10 of the SH3-1 domain of CD2AP is indispensable for CD2AP function in vivo. We found that the binding affinity of nephrin to CD2AP is significantly enhanced in the absence of Y10; however, unexpectedly, this increased affinity leads not to stabilization but to functional impairment of the glomerular filtration barrier. CONCLUSIONS: Our findings provide insight into CD2AP and its phosphorylation in the context of slit diaphragm functionality, and indicate a fine-tuned affinity balance of CD2AP and nephrin that is influenced by receptor tyrosine kinase stimulation.
CRIS-Team Scopus Importer:2019-07-26
Keywords: CD2AP; nephrin; Phosphorylation; podocyte

Whole-Exome sequencing enables a precision medicine approach for kidney transplant recipients - Mann, Nina; Braun, Daniela A.; Amann, Kassaundra; Tan, Weizhen; Shril, Shirlee; Connaughton, Dervla M.; Nakayama, Makiko; Schneider, Ronen; Kitzler, Thomas M.; Van Der Ven, Amelie T.; Chen, Jing; Ityel, Hadas; et al. (Journal of the American Society of Nephrology, 2019)
Background Whole-exome sequencing (WES) finds a CKD-related mutation in approximately 20% of patients presenting with CKD before 25 years of age. Although provision of amolecular diagnosis could have important implications for clinical management, evidence is lacking on the diagnostic yield and clinical utility of WES for pediatric renal transplant recipients. Methods To determine the diagnostic yield ofWES in pediatric kidney transplant recipients, we recruited 104 patients who had received a transplant at Boston Children's Hospital from 2007 through 2017, performed WES, and analyzed results for likely deleterious variants in approximately 400 genes known to cause CKD. Results By WES, we identified a genetic cause of CKD in 34 out of 104 (32.7%) transplant recipients. The likelihood of detecting a molecular genetic diagnosis was highest for patients with urinary stone disease (three out of three individuals), followed by renal cystic ciliopathies (seven out of nine individuals), steroidresistant nephrotic syndrome (nine out of 21 individuals), congenital anomalies of the kidney and urinary tract (ten out of 55 individuals), and chronic glomerulonephritis (one out of seven individuals). WES also yielded a molecular diagnosis for four out of nine individuals with ESRD of unknown etiology. The WESrelated molecular genetic diagnosis had implications for clinical care for five patients. Conclusions Nearly one third of pediatric renal transplant recipients had a genetic cause of their kidney disease identified by WES. Knowledge of this genetic information can help guide management of both transplant patients and potential living related donors.
Created from Fastlane, Scopus look-up

Whole exome sequencing frequently detects a monogenic cause in early onset nephrolithiasis and nephrocalcinosis - Daga, Ankana; Majmundar, Amar J.; Braun, Daniela A.; Gee, Heon Yung; Lawson, Jennifer A.; Shril, Shirlee; Jobst-Schwan, Tilman; Vivante, Asaf; Schapiro, David; Tan, Weizhen; Warejko, Jillian K.; Widmeier, Eugen; et al. (Kidney International, 2018)
The incidence of nephrolithiasis continues to rise. Previously, we showed that a monogenic cause could be detected in 11.4% of individuals with adult-onset nephrolithiasis or nephrocalcinosis and in 16.7-20.8% of individuals with onset before 18 years of age, using gene panel sequencing of 30 genes known to cause nephrolithiasis/nephrocalcinosis. To overcome the limitations of panel sequencing, we utilized whole exome sequencing in 51 families, who presented before age 25 years with at least one renal stone or with a renal ultrasound finding of nephrocalcinosis to identify the underlying molecular genetic cause of disease. In 15 of 51 families, we detected a monogenic causative mutation by whole exome sequencing. A mutation in seven recessive genes (AGXT, ATP6V1B1, CLDN16, CLDN19, GRHPR, SLC3A1, SLC12A1), in one dominant gene (SLC9A3R1), and in one gene (SLC34A1) with both recessive and dominant inheritance was detected. Seven of the 19 different mutations were not previously described as disease-causing. In one family, a causative mutation in one of 117 genes that may represent phenocopies of nephrolithiasis-causing genes was detected. In nine of 15 families, the genetic diagnosis may have specific implications for stone management and prevention. Several factors that correlated with the higher detection rate in our cohort were younger age at onset of nephrolithiasis/nephrocalcinosis, presence of multiple affected members in a family, and presence of consanguinity. Thus, we established whole exome sequencing as an efficient approach toward a molecular genetic diagnosis in individuals with nephrolithiasis/nephrocalcinosis who manifest before age 25 years.
Created from Fastlane, Scopus look-up
Keywords: monogenic cause; nephrocalcinosis; nephrolithiasis; whole exome sequencing

Whole exome sequencing identified ATP6V1C2 as a novel candidate gene for recessive distal renal tubular acidosis - Jobst-Schwan, Tilman; Klambt, Verena; Tarsio, Maureen; Heneghan, John F.; Majmundar, Amar J.; Shril, Shirlee; Buerger, Florian; Ottlewski, Isabel; Shmukler, Boris E.; Topaloglu, Rezan; Hashmi, Seema; Hafeez, Farkhanda; et al. (Kidney International, 2020)
Distal renal tubular acidosis is a rare renal tubular disorder characterized by hyperchloremic metabolic acidosis and impaired urinary acidification. Mutations in three genes (ATP6V0A4, ATP6V1B1 and SLC4A1) constitute a monogenic causation in 58-70% of familial cases of distal renal tubular acidosis. Recently, mutations in FOXI1 have been identified as an additional cause. Therefore, we hypothesized that further monogenic causes of distal renal tubular acidosis remain to be discovered. Panel sequencing and/or whole exome sequencing was performed in a cohort of 17 families with 19 affected individuals with pediatric onset distal renal tubular acidosis. A causative mutation was detected in one of the three “classical” known distal renal tubular acidosis genes in 10 of 17 families. The seven unsolved families were then subjected to candidate whole exome sequencing analysis. Potential disease causing mutations in three genes were detected: ATP6V1C2, which encodes another kidney specific subunit of the V-type proton ATPase (1 family); WDR72 (2 families), previously implicated in V-ATPase trafficking in cells; and SLC4A2 (1 family), a paralog of the known distal renal tubular acidosis gene SLC4A1. Two of these mutations were assessed for deleteriousness through functional studies. Yeast growth assays for ATP6V1C2 revealed loss-of-function for the patient mutation, strongly supporting ATP6V1C2 as a novel distal renal tubular acidosis gene. Thus, we provided a molecular diagnosis in a known distal renal tubular acidosis gene in 10 of 17 families (59%) with this disease, identified mutations in ATP6V1C2 as a novel human candidate gene, and provided further evidence for phenotypic expansion in WDR72 mutations from amelogenesis imperfecta to distal renal tubular acidosis.
Created from Fastlane, Scopus look-up
Keywords: distal tubule; pediatric nephrology; renal acidification; renal tubular acidosis

Whole-exome sequencing identifies causative mutations in families with congenital anomalies of the kidney and urinary tract - Van Der Ven, Amelie T.; Connaughton, Dervla M.; Ityel, Hadas; Mann, Nina; Nakayama, Makiko; Chen, Jing; Vivante, Asaf; Hwang, Daw-Yang; Schulz, Julian; Braun, Daniela A.; Schmidt, Johanna Magdalena; Schapiro, David; et al. (Journal of the American Society of Nephrology, 2018)
Background Congenital anomalies of the kidney and urinary tract (CAKUT) are the most prevalent cause of kidney disease in the first three decades of life. Previous gene panel studies showed monogenic causation in up to 12% of patients with CAKUT. Methods We applied whole-exome sequencing to analyze the genotypes of individuals from 232 families with CAKUT, evaluating for mutations in single genes known to cause human CAKUT and genes known to cause CAKUT in mice. In consanguineous or multiplex families, we additionally performed a search for novel monogenic causes of CAKUT. Results In 29 families (13%), we detected a causative mutation in a known gene for isolated or syndromic CAKUT that sufficiently explained the patient's CAKUT phenotype. In three families (1%), we detected a mutation in a gene reported to cause a phenocopy of CAKUT. In 15 of 155 families with isolated CAKUT, we detected deleterious mutations in syndromic CAKUT genes. Our additional search for novel monogenic causes of CAKUT in consanguineous and multiplex families revealed a potential single, novel monogenic CAKUT gene in 19 of 232 families (8%). Conclusions We identified monogenic mutations in a known human CAKUT gene or CAKUT phenocopy gene as the cause of disease in 14% of the CAKUT families in this study. Whole-exome sequencing provides an etiologic diagnosis in a high fraction of patients with CAKUT and will provide a new basis for the mechanistic understanding of CAKUT.
Created from Fastlane, Scopus look-up

Whole exome sequencing of patients with steroid-resistant nephrotic syndrome - Warejko, Jillian K.; Tan, Weizhen; Daga, Ankana; Schapiro, David; Lawson, Jennifer A.; Shril, Shirlee; Lovric, Svjetlana; Ashraf, Shazia; Rao, Jia; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; et al. (Clinical Journal of the American Society of Nephrology, 2018)
Background and objectives Steroid-resistant nephrotic syndrome overwhelmingly progresses to ESRD. More than 30 monogenic genes have been identified to cause steroid-resistant nephrotic syndrome. We previously detected causative mutations using targeted panel sequencing in 30% of patients with steroid-resistant nephrotic syndrome. Panel sequencing has a number of limitations when compared with whole exome sequencing. We employed whole exome sequencing to detect monogenic causes of steroid-resistant nephrotic syndrome in an international cohort of 300 families. Design, setting, participants, & measurements Three hundred thirty-five individuals with steroid-resistant nephrotic syndrome from 300 families were recruited from April of 1998 to June of 2016. Age of onset was restricted to <25 years of age. Exome data were evaluated for 33 known monogenic steroid-resistant nephrotic syndrome genes. Results In 74 of 300 families (25%), we identified a causative mutation in one of 20 genes known to cause steroid-resistant nephrotic syndrome. In 11 families (3.7%), we detected a mutation in a gene that causes a phenocopy of steroid-resistant nephrotic syndrome. This is consistent with our previously published identification of mutations using a panel approach. We detected a causative mutation in a known steroid-resistant nephrotic syndrome gene in 38% of consanguineous families and in 13% of nonconsanguineous families, and 48% of children with congenital nephrotic syndrome. A total of 68 different mutations were detected in 20 of 33 steroid-resistant nephrotic syndrome genes. Fifteen of these mutations were novel. NPHS1, PLCE1, NPHS2, and SMARCAL1 were the most common genes in which we detected a mutation. In another 28% of families, we detected mutations in one or more candidate genes for steroid-resistant nephrotic syndrome. Conclusions Whole exome sequencing is a sensitive approach toward diagnosis of monogenic causes of steroid-resistant nephrotic syndrome. A molecular genetic diagnosis of steroid-resistant nephrotic syndrome may have important consequences for the management of treatment and kidney transplantation in steroid-resistant nephrotic syndrome.
Created from Fastlane, Scopus look-up
Keywords: Child; Exome; Genetic renal disease; Humans; Kidney failure; chronic; Kidney transplantation; Molecular genetics; Mutation; Nephrosis; congenital; Nephrotic syndrome; Pediatric; Phenotype; Renal insufficiency; chronic